Reactive cysteine persulfides and S-polythiolation regulate oxidative stress and redox signaling - Ida, Tomoaki (National Academy of Sciences, 2014)
Using methodology developed herein, it is found that reactive persulfides and polysulfides are formed endogenously from both small molecule species and proteins in high amounts in mammalian cells and tissues. These reactive sulfur species were biosynthesized by two major sulfurtransferases: cystathionine β-synthase and cystathionine γ-lyase. Quantitation of these species indicates that high concentrations of glutathione persulfide (perhydropersulfide >100 μM) and other cysteine persulfide and polysulfide derivatives in peptides/proteins were endogenously produced and maintained in the plasma, cells, and tissues of mammals (rodent and human). It is expected that persulfides are especially nucleophilic and reducing. This view was found to be the case, because they quickly react with H(2)O(2) and a recently described biologically generated electrophile 8-nitroguanosine 3′,5′-cyclic monophosphate. These results indicate that persulfides are potentially important signaling/effector species, and because H(2)S can be generated from persulfide degradation, much of the reported biological activity associated with H(2)S may actually be that of persulfides. That is, H(2)S may act primarily as a marker for the biologically active of persulfide species.